Clinical and radiological evaluation of delayed and early loading of single-tooth implant placement: A 6-month, prospective, randomized, follow-up clinical study - Santhosh Sekar; Thangakumaran Suthanthiran; Arthiie Thangavelu; Sasi Kumar Karupannan; Fairlin Prem; Dhivya Rajendran (Wolters Kluwer Medknow Publications, 2019)
Purpose: The purpose of the study was to compare delayed and early loaded single-tooth implant technique. Materials and Methods: A randomized, prospective clinical trial was conducted to evaluate the clinical and radiological parameters of delayed and early loading of single-tooth implant placement. Fourteen male or female patients were selected randomly, who had single tooth missing in mandibular posterior region. A delayed implant placement technique was followed in these regions. A Hi-Tech implant (Life Care Implants) was performed. The patients were divided into two groups: delayed loading group and early loading group. In delayed loading groups, implants were loaded after 3 months, and in early loading groups, implants were loaded within 7 days to 2 months. Soft tissue and radiological bone loss were assessed at baseline, 3 months, and 6 months. The parameters assessed were plaque index, gingival index, probing pocket depth, thickness of peri-implant mucosa, and bone loss (radiographically). Results: The results show that there was no statistical difference in indexes taken between delayed loading and early loading groups. Conclusion: In this study, after first 6 months there was no difference in success rate between delayed loading or early loading of implants. This study also showed that more bone loss occurred around delayed loading implants. So it can be concluded that early loading technique can be successfully practiced instead of delayed loading of implants.